Self-reported ongoing adherence to diet is associated with lower depression, fatigue, and disability, in people with multiple sclerosis - Yu, Maggie; Jelinek, George; Simpson-Yap, Steve; Neate, Sandra; Nag, Nupur (Frontiers in Nutrition, 2023)
Increasingly, healthy diets are being shown to have positive associations with health outcomes in people with multiple sclerosis (pwMS). However, maintaining a specific MS-diet can be a challenge, therefore assessing whether persistent adherence to a MS-diet is associated with maintenance of improved health outcomes, is important. We assess associations between levels of adherence to MS-diets with clinical outcomes of fatigue, depression, and disability, in pwMS. Data from an international population of pwMS (n=671) were analysed. Self-assessed adherence to six MS-diets (Ashton Embry Best Bet, McDougall, Overcoming MS (OMS), Paleolithic (Paleo), Swank, and Wahls Elimination) were queried at two timepoints. Adherence to OMS- and Swank-diet were individually assessed, and other diets combined. Levels of adherence were defined as persistent-adherence at both timepoints; partial-adherence at one timepoint; and non-adherence at neither timepoint. Associations between persistent-adherence to MS-diet and fatigue, depression, and disability, were assessed by log-binomial regression models adjusted for confounders. Fifty-four percent of pwMS self-reported ≥12-month adherence to a MS-diet, 44% to OMS-, 7% to Swank-, and 5% to Other-diet at 5-year. Persistent-adherence to OMS-diet (33%) was associated with lower fatigue and disability than partial (ceased)-adherence, and fewer depressive symptoms than both non- and partial (ceased)-adherence. No associations were observed between adherence to Swank- or Other-diet and health outcomes. Adherence to OMS-diet has potential benefits on MS outcomes, but continuation is likely required to maintain the benefits. Support for pwMS to maintain long-term adherence to MS-diets is warranted. Further studies are needed to determine whether comparable benefits are observed with other MS-diets.